Studies on the control of high-gain DC-DC boost converters - Jiang, Wentao (2018)
The traditional dc-dc boost converter has been widely applied in industrial applications. However, due to the parasitic resistance of the inductor and the serious reverse-recovery problem, the voltage gain of this converter is very limited. To solve this problem, many high voltage gain dc-dc boost converters have been proposed in the last decade. The high voltage gain dc-dc boost converters can be roughly separated as isolated converters and non-isolated converters. Since most of the isolated converters suffer from large amount of power losses caused by the leakage current problem, the non-isolated converters are more preferred in applications where electrical isolation is not necessary.